INTERNATIONAL STRATEGIC MANAGEMENT (STUDY IN THE UNITED STATES OF AMERICA) - Maisyura; Rico Nur Ilham; Lidya Beru Tarigan; Eka Astria; Etia Farianti (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
International strategic management is a comprehensive and ongoing process of management planning aimed at developing and implementing strategies that enable businesses to compete effectively in an international environment. The process of developing an international strategy is of course often referred to as "strategic planning". Strategic planning is usually the responsibility of senior management at company headquarters and in the company's domestic and international operating branches. Most large companies also have population planners who provide technical assistance to top management in formulating strategy. For example, five Disney planners first collected the demographic and economic data policy makers needed, and then used that data to select France as the location for Euro Disney. International strategic management leads to the formulation of various international strategies. It is a comprehensive framework for achieving the company's fundamental goals. Conceptually, there are many similarities between developing strategic capabilities in one country and developing competitive strategies in many countries. According to Hill and Jones (2012), international strategic management is “the process of establishing, developing, and implementing corporate strategic actions aimed at gaining competitive advantage in global markets”. Method Descriptive qualitative method is a research method used to gain a deep understanding of phenomena through description, interpretation and analysis of qualitative data.